2016
DOI: 10.1002/prot.25167
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative electrostatic analysis of adenylyl cyclase for isoform dependent regulation properties

Abstract: The enzyme adenylyl cyclase (AC) plays a pivotal role in a variety of signal transduction pathways inside the cell, where it catalyzes the cyclization of adenosine triphosphate (ATP) into the second-messenger cyclic adenosine monophosphate (cAMP). Among other roles, AC regulates processes involved in neural plasticity, innervation of smooth muscles of the heart and the endocrine system of the pancreas. The functional diversity of AC is manifested in its different isoforms, each having a specific regulation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…Previously, we have performed electrostatic analyses of mouse AC isoforms, to identify regions of electrostatic similarity within similarly regulated isoforms [48]. In that work, we showed that the molecular electrostatic potentials surrounding ACs 1, 5 and 6 in aqueous solution were very similar in the Gα i binding region of AC5, suggesting that the location of binding, and the bound orientation, of Gα i on ACs 1 and 6, could be similar.…”
Section: Discussionmentioning
confidence: 86%
“…Previously, we have performed electrostatic analyses of mouse AC isoforms, to identify regions of electrostatic similarity within similarly regulated isoforms [48]. In that work, we showed that the molecular electrostatic potentials surrounding ACs 1, 5 and 6 in aqueous solution were very similar in the Gα i binding region of AC5, suggesting that the location of binding, and the bound orientation, of Gα i on ACs 1 and 6, could be similar.…”
Section: Discussionmentioning
confidence: 86%
“…The activity of AC isoforms are differentially regulated by stimulatory and inhibitory G proteins. 14 Group III ACs AC5 and AC6 are classically activated by Gαs or Gβγ, 60 while regulated negatively by Gαi, 14 calcium 61 and protein kinases. 30,31,62 Gβγ interactions with AC6 and AC5 require initial Gαs binding, and can also augment forskolin-mediated activation 63 ; but Gβγ binding to AC5 and to AC6 are differently regulated despite the structural similarity of these two AC isoforms, highlighting the relevance of individual residues governing these specific molecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous peptide sequences in each strain are indicated in each plot. Solvent-accessible surfaces with electrostatic potential representations in the indicated ranges [down to −61 kcal/(mol· e ) in red and up to +61 kcal/(mol· e ) in blue] were calculated using the APBS solver ( 57 ) in multipipsa4.0.2 ( 35 ). All calculations were performed at 150 mM ionic strength, 298.15 Kelvin, pH 7.2, protein dielectric 1.0, and solvent dielectric 78 with a probe radius of 1.4 Å.…”
Section: Resultsmentioning
confidence: 99%
“…To perform a structure-based classification of SARS-CoV-2 peptide/HLA-A * 02:01 complexes according to their TCR interaction features and compare their surfaces to homologous peptides from common cold coronavirus strains, we (i) aligned respective protein sequences (specifically, orf1ab, membrane, spike, envelope , and nucleocapsid proteins) from all strains using Clustal Omega, (ii) extracted 395 (out of 439) epitopes of length 9 from common cold coronavirus strains based on sequence homology with SARS-CoV-2 binders predicted by NetMHCpan-4.0 using default %rank cut-off values (44/439 SARS-CoV-2 epitope sequences are from proteins not considered), (iii) filtered out 141 epitopes containing insertions and deletions in the sequence alignment and those that do not have homologous sequences across all strains of common cold coronaviruses, (iv) modeled structures of the remaining 254 peptide/HLA-A * 02:01 complexes from each strain using RosettaMHC, and (v) performed a comparison of surface electrostatic potentials between each SARS-CoV-2 pMHC structure and its corresponding common cold coronavirus homologs using multipipsa4.0.2 ( 35 ). The multipipsa4.0.2 software applies the Adaptive Poisson-Boltzmann Solver (or APBS) ( 36 ) method to first compute electrostatic potentials, and then compares the potentials using the Protein Interaction Property Similarity Analysis (or PIPSA) protocol ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation